Effect of replacement of fish meal by corn gluten meal on growth and thyroid hormone contents in serum of Carassius auratus gibelio - HUA Xue-ming; WANG Jun; LIU Xing-guo; ZHU Zhan-ying; YU ning; ZHOU Hong-qi (浙江大学学报. 农业与生命科学版)
An experiment was conducted to evaluate the use of corn gluten meal (CGM) as a dietary protein for Carassius auratus gibelio. Four kinds of isocaloric, isonitrogenous diets were formulated to contain 0% (control), 4%, 8% and 12% of corn gluten meal (CGM), replacing 0%, 33.33%, 66.67% and 100% of fish meal respectively. The fish with initial average body mass of (13.68±1.77) g were fed in a recirculation aquaculture system indoors for 60 days. The growth, serum triiodothyronine (T3) and thyroxine (T4) contents of C. auratus gibelio were determined. The results showed that feed conversion ratio (FCR) of control and 8% CGM groups were significantly higher than that of 4% and 12% CGM groups (P<0.05). CGM did not significantly affect on growth of allogynogenetic silver crucian carp. CGM did not significantly affect T 3 content in serum from 30th to 60th day, but T3 content of the control group was significantly higher than the other groups (P<0.05) in 15th day. During the first 30 days in the experiment, T4 content in serum of the control group was significantly higher than that of 12% CGM group, but had no significant difference compared with 4% and 8% CGM groups. There were no significant effects on T 4 contents among each group in 60th day. At the end of the feeding test, the growth and T3, T4 contents in serum of C. auratus gibelio among four groups had same trends. All the results indicate that the appropriate dosage of CGM is 4% -8%, replacing 33.33%-66.67% of fish meal of the diets in this experiment.